Mother’s perseption and attitudes on exclusive breastfeeding among traditional market traders - Ariani, Peny; Lipoeto, Nur Indrawaty; Chundrayetti, Eva; Malini, Hema (Institute of Computer Science (IOCS), 2025)
The benefits of breastfeeding for infants are well documented. One factor that contributes to suboptimal exclusive breastfeeding is the presence of working mothers. However, studies have revealed that employers tend to hold negative perceptions of breastfeeding, particularly for those working in the informal sector. The objective of this study was to examine the perspectives of mothers engaged in informal employment in North Sumatra and to identify the factors that influence their decision to exclusively breastfeed. A qualitative study was conducted with the participation of formal workers who were traders in traditional markets. In this study, mothers with children aged 0-2 years old who work as traders in traditional markets were recruited to participate in focus group discussions (FGDs) conducted in the local language which lasted between 45 and 60 minutes, were audio recorded and transcribed. The data were analyzed using a content analysis approach. The decision to exclusively breastfeed is influenced by a number of factors for mothers who work as traditional market traders. These can be grouped into three sub-themes: perceived benefits of breast milk and positive breastfeeding, support from family and friends, and misinformation related to breastfeeding behaviour and self-efficacy of breastfeeding mothers. Peer support for breastfeeding is a highly valuable study intervention. The health system and health workers facilitate the expansion of exclusive breastfeeding peer support. Highlight the benefits of exclusive breastfeeding across all socioeconomic groups and advocate for more conducive policies.